Assessment of Heavy Metals Using the Enrichment Factor and Geoaccumulation Index in Menjer Lake, a Tropical Volcanic Lake - Fadlillah, Lintang; Widyastuti, M; Rachmawati, Alfina Ayu; Ulfa, Azura (BRIN Publishing, 2024)
Lakes are recognized as vulnerable to pollution, including Menjer Lake, whose catchment area is dominated by agricultural lands and features floating net cages in the water body. The heightened contamination risk within the lake primarily stems from the accumulation of heavy metals, compounds known for their profound toxicity. The high-level concentration of heavy metal in sediment aligns with the level of water toxicity, underscoring the urgent need for thorough assessment and monitoring. The research focused on assessing heavy metal concentration and distribution through spatial analysis. Toxicity levels were evaluated using the enrichment factor (EF) and Geoaccumulation Index (Igeo). This study collected eight samples each during the rainy season of 2022 and 2023. The heavy metals were tested using an Atomic Absorption Spectrophotometer (AAS), including Pb, Cd, Cr, Fe, Al, and Cu. Comparatively, the mean concentration of heavy metals in 2023 was slightly higher for Fe and Al than in 2022. Moreover, Cd was not detected in either 2022 or 2023. The variety of land use and land cover has consequences on the spatial distribution of toxicity levels, showing an influential correlation between Al, Pb, and Fe metals with locations associated with cropland and floating net cages. Additionally, highly steep slopes significantly affected erosions that induced sediment from agricultural land use, further underscoring the multifaceted nature of environmental risk factors.